(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the pedagogical, psychological, and social characteristics of teaching English to students in inclusive education settings. It highlights the importance of adapted methodologies, individualized approaches, and communicative methods for students with special educational needs. The paper also explores the role of psychological support and factors influencing students’ socialization in the learning process. The significance of inclusive education in promoting societal development and democratizing the educational system is emphasized.